Peran bahasa asing dalam era globalisasi: Tantangan dan peluang - Hotimah, Emah (Maliki Interdisciplinary Journal, 2024)
This article discusses the role of foreign languages in the era of globalization, highlighting its challenges and opportunities. Challenges include threats to the national language, foreign cultural influences and grammatical difficulties. On the other hand, opportunities include access to global information, international careers, intercultural skills, and strong personal and professional relationships. In an increasingly connected world, the use of foreign languages has an important role to play in overcoming challenges and capitalizing on opportunities. Thus, it is important to promote strong and sustainable foreign language education to enable people to compete in an increasingly complex global environment.